Whatever it takes: The real effects of unconventional monetary policy - Viral Acharya; Tim Eisert; Christian Eufinger; Christian Hirsch (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
Launched in Summer 2012, the European Central Bank (ECB)'s Outright Monetary Transactions (OMT) program indirectly recapitalized European banks through its positive impact on periphery sovereign bonds. However, the stability reestablished in the banking sector did not fully translate into economic growth. We document zombie lending by banks that remained undercapitalized even post-OMT. In turn, firms receiving loans used these funds not to undertake real economic activity such as employment and investment but to build up cash reserves. Creditworthy firms in industries with a high zombie firm prevalence suffered significantly from this credit misallocation, which further slowed down the economic recovery.
urn:nbn:de:hebis:30:3-418716
Keywords: 330; Unconventional Monetary Policy; Real Effects; Zombie Lending